Answer:
1) A = (3 + 5·i) + (2 - 3·i)
2) A = (-3 + 5·i) + (-2 - 3·i)
3) A = (-3 + 5·i) + (2 + 3·i)
4) A = (3 - 5·i) + (2 + 3·i)
Explanation:
1) For the first chart, we have;
To go from the start point to get the new line, we add the coordinates of the red line end point to the coordinates of the starting line end point as follows
A = (3 + 5·i) + (2 - 3·i)
2) For the second chart, we have;
To go from the start point to get the new line, we add the coordinates of the red line end point to the coordinates of the starting line end point as follows
A = (-3 + 5·i) + (-2 - 3·i)
3) For the third chart, we have;
To go from the start point to get the new line, we add the coordinates of the red line end point to the coordinates of the starting line end point as follows
A = (-3 + 5·i) + (2 + 3·i)
4) For the fourth chart, we have;
To go from the start point to get the new line, we add the coordinates of the red line end point to the coordinates of the starting line end point as follows
A = (3 - 5·i) + (2 + 3·i)